A Numerical Procedure for the Virtual Compression after Impact Analysis. Issue 4 (July 2015) - Borrelli, Rosario; Franchitti, Stefania; Di Caprio, Francesco; Romano, Fulvio; Mercurio, Umberto
The aim of the proposed research activity is to investigate on the structural behaviour of composite plates in order to develop numerical models able to describe their damage resistance to impact loads and their damage tolerance through compression after impact (CAI) test. The present paper presents a two-step simulation approach for determining the residual strength after a low velocity impact on a composite laminate of aeronautical interest. The first step is aimed at determining the damage extent after the impact event and it is performed by using an explicit finite element code. Hence, the damage status induced by the impact is transferred to the finite element model for the virtual compression after impact test which is simulated in a second step by using an implicit finite element code. Numerical results, in terms of force vs. displacement impact curve, damage envelope and reaction vs. applied strain compression curve, were compared to the experimental ones for validation purpose.